Flora of Bahia - Giulietti, Ana Maria; Queiroz, Luciano P. de; Silva, Tânia Regina dos Santos; França, Flávio; Guedes, Maria Lenise; Amorim, André Márcio (SITIENTIBUS série Ciências Biológicas, 2006)
The Flora of Bahia Project was started in 1997 following the guidelines provided by the Sociedade de Botânica do Brasil to update data on the Flora of Brazil. It is the product of several years of sampling and identification of specimens in Bahia State, and it reflects the joint effort of various institutions and researchers. By means of independent works, the Flora is presented in this issue of Sitientibus série Ciências Biológicas as well as in the next ones. Description is given at the level of family or genus following the established pattern. Meanwhile, the program of sampling goes on in order to enlarge the number of samples within the state. These will focus mainly on the study of underestimate areas, on the formation of new taxonomists, and on projects for better understanding, using, and conserving the flora.